City Branding Dimensions, Strategies, and Obstacles: A Literature Review - Zahrah, Fatimatuz (Research and Development Agency Ministry of Home Affairs, 2023)
City branding is carried out to develop cities, attract tourism, introduce the city's wealth, and improve the community's quality of life. Various ways are done to show the uniqueness and distinctiveness that is owned. Some city branding efforts are seasonal, in vain, fail, and must be clarified for the public. This study aims to analyze the dimensions of city branding, strategies to build city branding, and obstacles and solutions in building city branding. This research is a critical literature review reviewing 35 articles from 2017 to 2023 and focusing on the progress of research on city branding. The formulation and findings of this study are the dimensions of city branding, namely tourist attraction, security and public services, and public policy and government coordination with the community. The city branding strategy can be carried out in five ways: introducing cultural diversity, culinary diversity, natural wealth, improving public services and security, and promoting and building a mascot. The obstacles to city branding are the need for coordination between the government and the community, inadequate facilities and infrastructure, and unclear concepts related to the city branding used. The implications of this research indicate that city branding efforts must be integrated between government policies and community participation. Full involvement of the government and good cooperation with community members and Small and Medium Enterprise (creative community groups) is recommended to be one of the efforts to build city branding in various cities and is also recommended for city branding program plans.